Partners and close family members of long‐term cancer survivors: health status, psychosocial well‐being and unmet supportive care needs. Issue 1 (9th September 2011) - Turner, Daniel; Adams, Eike; Boulton, Mary; Harrison, Sian; Khan, Nada; Rose, Peter; Ward, Alison; Watson, Eila K.
Abstract Background A cancer diagnosis can have a profound impact on partners and close family members of patients. Little is currently known about the long‐term impact. Objectives The objective of this study is to describe health status, levels of anxiety and depression, unmet supportive care needs and positive outcomes in the partners/family members of breast, prostate and colorectal cancer survivors 5–16 years post‐diagnosis. Methods Patients in a linked study were asked to invite a partner or other close family member to complete a self‐administered postal questionnaire. Data were analysed by cancer site and time since diagnosis. Matched comparisons were made between cancer patients in the linked study and their partners. Results An expression of interest was received from 330 partners/family members, and 257 questionnaires (77.9%) were returned. Health status and levels of anxiety and depression were comparable with population norms. Respondents reported an average of 2.7 unmet needs from 34 possible options. Hospital parking, information about familial risk, help managing fear of recurrence and coordination of care were the most cited unmet needs. There was little variation in health status, psychological morbidity and unmet needs by cancer site or time since diagnosis. Concordance between patients and partners was low for anxiety but higher with respect to positive outcomes and some unmet needs. Conclusions Most partners/family members of long‐term cancer survivors report few ongoing issues. However, a small proportion (<10%) have high levels of anxiety and/or moderate or strong unmet needs. Strategies for identifying this group and addressing their needs are required, while allowing the majority to resume normal life. Copyright © 2011 John Wiley & Sons, Ltd.